Analisis Penerapan Kurikulum Merdeka dalam Membentuk Profil Pelajar Pancasila pada Pelajaran Agama Islam Kelas VII MTsS Teladan Gebang - Ribka Serly Lestari; Muhizar Muchtar; Zaifatur Ridha (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study aims to analyse the application of Merdeka Curriculum in the formation of the Pancasila Student Profile in Islamic Religion lessons in class VII MTsS Teladan Gebang. This research method uses a qualitative approach with a case study method, this research collects data through observation, interviews, and documentation to understand how this curriculum is implemented in the context of religious learning. The results showed that MTsS Teladan Gebang has successfully adapted the Merdeka Curriculum in accordance with the Decree of the Minister of Education No. 56 of 2022, by giving teachers the freedom to adjust learning methods. The character building of Pancasila students is carried out through various activities that emphasise religious and social values, such as joint prayers, congregational prayers, and creative projects. The implementation of this curriculum shows success in integrating Pancasila values into students‘ daily activities, as well as adaptive assessment to monitor students’ overall development. This research shows that Merdeka Curriculum can effectively support students' character and skill development, making them religious, responsible and Pancasila-minded learners.